Genome-wide mapping of large deletions and their population-genetic properties in dairy cattle - Mesbah-Uddin, Md; Guldbrandtsen, Bernt; Iso-Touri, Terhi; Vilkki, Johanna; De Koning, Dirk-Jan; Boichard, Didier; Lund, Mogens Sandø; Sahana, Goutam (Oxford University Press, 2018)
Large genomic deletions are potential candidate for loss-of-function, which could be lethal as homozygote. Analysing whole genome data of 175 cattle, we report 8,480 large deletions (199 bp–773 KB) with an overall false discovery rate of 8.8%; 82% of which are novel compared with deletions in the dbVar database. Breakpoint sequence analyses revealed that majority (24 of 29 tested) of the deletions contain microhomology/homology at breakpoint, and therefore, most likely generated by microhomology-mediated end joining. We observed higher differentiation among breeds for deletions in some genic-regions, such as ABCA12, TTC1, VWA3B, TSHR, DST/BPAG1, and CD1D. The genes overlapping deletions are on average evolutionarily less conserved compared with known mouse lethal genes (P-value = 2.3 × 10−6). We report 167 natural gene knockouts in cattle that are apparently nonessential as live homozygote individuals are observed. These genes are functionally enriched for immunoglobulin domains, olfactory receptors, and MHC classes (FDR = 2.06 × 10−22, 2.06 × 10−22, 7.01 × 10−6, respectively). We also demonstrate that deletions are enriched for health and fertility related quantitative trait loci (2-and 1.5-fold enrichment, Fisher’s P-value = 8.91 × 10−10 and 7.4 × 10−11, respectively). Finally, we identified and confirmed the breakpoint of a ∼525 KB deletion on Chr23:12,291,761-12,817,087 (overlapping BTBD9, GLO1 and DNAH8), causing stillbirth in Nordic Red Cattle.
Keywords: structural variants; whole genome sequence; loss-of-function; lypsykarja; rakenneominaisuudet; dairy cattle; variants; genomes; population genetics